Association between inflammatory bowel disease, nephrolithiasis, tubulointerstitial nephritis, and chronic kidney disease: A propensity score‐matched analysis of US nationwide inpatient sample 2016–2018 - Zheng, Wei Wei; Zhou, Quan; Xue, Meng Li; Yu, Xing; Chen, Jin Tong; Ao, Lu; Wang, Cheng Dang (Journal of digestive diseases, 2023)
Objectives The incidence and prevalence of inflammatory bowel disease (IBD), mainly including ulcerative colitis (UC) and Crohn's disease (CD), are increasing globally. We aimed to evaluate the potential association between IBD and nephrolithiasis, tubulointerstitial nephritis, and chronic kidney disease (CKD). Methods Data of hospitalized adults ≥20 years of age were extracted from the U.S. National Inpatient Sample (NIS) during 2016–2018. Patients with UC, CD, or CKD were identified through the International Classification of Diseases, Tenth Revision (ICD‐10) codes. Propensity score matching (PSM) analysis (1:1) was conducted to balance the characteristics between groups. Logistic regression analyses were performed to determine the relationships between UC or CD and kidney conditions. Results Three cohorts were included for analysis after PSM analysis. Cohorts 1, 2 and 3 contained 235 262 subjects (117 631 with CD or without IBD), 140 856 subjects (70 428 with UC or without IBD), and 139 098 subjects (69 549 with CD or UC), respectively. Multivariate analysis revealed that compared to non‐IBD individuals, CD patients were significantly associated with greater odds for nephrolithiasis (adjusted odds ratio [aOR] 2.25, 95% confidence interval [CI] 2.08–2.43), tubulointerstitial nephritis (aOR 1.31, 95% CI 1.24–1.38), CKD at any stage (aOR 1.28, 95% CI 1.24–1.32), and moderate‐to‐severe CKD (aOR 1.22, 95% CI 1.17–1.26), while UC was associated with a higher rate of nephrolithiasis. Compared to UC, CD was associated with higher odds for all such kidney conditions. Conclusions Patients with CD are more likely to have nephrolithiasis, tubulointerstitial nephritis, CKD at any stage, and moderate‐to‐severe CKD compared to non‐IBD individuals. We assessed the relationship between inflammatory bowel disease (IBD), nephrolithiasis, tubulointerstitial nephritis, and chronic kidney disease (CKD) using a large, nationally representative U.S. database. This extensive epidemiological study indicates that individuals with Crohn's disease (CD) are particularly prone to having nephrolithiasis, tubulointerstitial nephritis, CKD at any stage, and moderate‐to‐severe CKD.